2005
DOI: 10.1210/en.2005-0768
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsins in the Ovine Uterus: Regulation by Pregnancy, Progesterone, and Interferon Tau

Abstract: Cathepsins (CTS) are peptidases that have biological roles in degrading extracellular matrix, catabolism of intracellular proteins, and processing of prohormones. Expression of CTSB, CTSD, CTSH, CTSK, CTSL, CTSS, and CTSZ genes was detected in the endometria of cyclic and early pregnant ewes with distinct temporal and spatial expression patterns. In the d 18 and 20 conceptus, expression of CTSB, CTSD, CTSL, and CTSZ mRNA was detected in the trophectoderm. Of particular note, CTSL mRNA was the most abundant CTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
87
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(90 citation statements)
references
References 42 publications
3
87
0
Order By: Relevance
“…Further, treatment of ovine endometrial LE and BEND cells with recombinant ovine IFNT induced RSAD2 and IFIH1 expression without a requirement for serum or P4 in the medium. In contrast, IFNT induction of several non-classical IFN-stimulated genes, such as LGALS15 (galectin 15), CTSL (cathespin L), and CST3 (cystatin C), in endometrial LE and sGE is dependent on P4 (Gray et al 2004, Song et al 2005, which is hypothesized to involve P4 downregulation of the PGR in those epithelia (Spencer et al 2004c, Gray et al 2006.…”
Section: Discussionmentioning
confidence: 99%
“…Further, treatment of ovine endometrial LE and BEND cells with recombinant ovine IFNT induced RSAD2 and IFIH1 expression without a requirement for serum or P4 in the medium. In contrast, IFNT induction of several non-classical IFN-stimulated genes, such as LGALS15 (galectin 15), CTSL (cathespin L), and CST3 (cystatin C), in endometrial LE and sGE is dependent on P4 (Gray et al 2004, Song et al 2005, which is hypothesized to involve P4 downregulation of the PGR in those epithelia (Spencer et al 2004c, Gray et al 2006.…”
Section: Discussionmentioning
confidence: 99%
“…As depicted in Fig. 1, temporal and spatial analyses of gene expression revealed that galectin 15 (LGALS15), cystatin C (CST3), and cathepsin L (CTSL) expression is initiated in the endometrial LE by day 12 and maintained to day 14 in both cyclic and pregnant ewes (Gray et al 2004, Song et al 2005, 2006a. Those genes are no longer expressed by day 16 in cyclic ewes, but their expression is further stimulated by IFNT from the conceptus in pregnant ewes.…”
Section: Hormonal Regulation Of Endometrial Function and Conceptus Dementioning
confidence: 99%
“…Recent studies found that LGALS15, CTSL, and CST3 are induced by progesterone and stimulated further by IFNT (Gray et al 2004, Song et al 2005, 2006a, Satterfield et al 2006. In most mammalian uteri, progesterone receptors (PGR) are expressed in endometrial epithelia and stroma during the early to mid-luteal phase, allowing direct regulation (induction or repression) of genes by progesterone.…”
Section: Pgr Regulation and Endometrial Gene Expressionmentioning
confidence: 99%
See 2 more Smart Citations